Pengaruh Sustainability Reporting Terhadap Nilai Perusahaan dengan Leverage sebagai Variabel Moderating - Galuh Artika Febriyanti (ITB AAS INDONESIA, 2021)
Sustainability reporting is a report that contains company assessment practices with due regard to economic, environmental and or social impacts. Currently, sustainability reporting is not required to be reported in Indonesia. The reporting that is required is the reporting of corporate social responsibility activities which is a separate of reporting and is not included in sustainability reporting. Research on the effect of sustainability reporting on firm value has been carried out both abroad and domestically. However, it was found that there was a research gap in previous studies. This study empirically examines the relationship between sustainability reporting, economic performance, environmental performance, and social performance on firm value. This study also examines the existence of the leverage variable as a variable that moderates sustainability reporting on firm value. Using multiple regression analysis and residual test showed that sustainability reporting and social performance did not have a significant effect on firm value. Meanwhile, economic performance and environmental performance have a significant effect on firm value. In addition, the result of this study also show that leverage can mediate the relationship between the disclosure of sustainability reporting and firm value.